LAW ENFORCEMENT AGAINST TELECOMMUNICATION CRIMES IN THE JURISDICTION OF THE CENTRAL JAVA REGIONAL POLICE - Hendratno, Kurniawan; Ma'ruf, Umar (Jurnal Hukum Khaira Ummah, 2023)
The jurisdiction of the Central Java Regional Police (Central Java Regional Police) can not be separated from the investigation of telecommunication crime, reports often appear in the area of Central Java Province. One of them is based on Police Report. Pol .: LP / A / 176 / V / 2014 / Jateng / Reskrimsus, dated May 8, 2014, alleged criminal act of selling / trading telecommunication equipments and equipments that do not comply with the required standards & rules of law and / or sell / Trade in telecommunication tools and equipment not equipped with certificate number or not in accordance with the certificate number, as referred to in Article 52 Act no. 36 of 1999 on Telecommunications and / or Article 62 paragraph (1) of Law no. 8 Year 1999 About Consumer Protection. That is why law enforcement based on applicable law needs to be applied so that in its implementation there is no disadvantaged party especially the consumer as the buyer. The legal sanction is contained in Article 62 paragraph (1) of Law Number 8 Year 1999 concerning Consumer Protection, namely a maximum imprisonment of 5 (five) years or a fine of not more than Rp 2,000,000,000.00 (two billion Rupiah). Society as a consumer must be empowered and understand things related to consumer protection. Therefore, the issue of consumer protection needs to be socially disaggregated so that if its rights have been violated it can be responsive and active in reporting offenses of crime as well as other consumer violations.Keywords: Telecommunication Criminal, Law, Telecommunication, Protection.